2017
DOI: 10.1590/abd1806-4841.20175056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative microscopic analysis of nail clippings from patients with cutaneous psoriasis and psoriatic arthritis

Abstract: BACKGROUNDThe nail involvement in psoriasis is related to psoriatic arthritis and may represent a predictor of the disease.OBJECTIVESTo analyze, through nail clipping, clinically normal and dystrophic nails of patients with cutaneous psoriasis and psoriatic arthritis.METHODSThis is a cross-sectional multicenter study, conducted between August 2011 and March 2012. Patients were divided into four groups: patients with cutaneous psoriasis and onychodystrophy, patients with cutaneous psoriasis and clinically norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…Anatomically, there is strong link between PsA and nail inflammation. Psoriatic changes in nails are a known risk factor for the development of arthritis 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, there is strong link between PsA and nail inflammation. Psoriatic changes in nails are a known risk factor for the development of arthritis 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that onycholysis, oil drop, and splinter hemorrhage, in particular, were significantly more prevalent in PsA patients. Fonseca et al found no statistical difference in NAPSI (Nail Psoriasis Severity Index) values among patients with or without psoriatic arthritis [ 20 ]. Perhaps, the type of nail involvement is more important than the severity of nail changes in terms of correlation with PsA.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still no clear explanation for this association and some believe that this association is limited only to distal interphalangeal (DIP) joints [ 22 ]. The suggested theories are (a) having a common (and yet unknown) autoantigen in both nail apparatus and synovial membrane, (b) anatomic connection between nail structures and DIP joints, and (c) the common role of trauma (Koebner phenomenon) in both nail and arthropathic psoriasis [ 20 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Recently, the use of nail clipping microscopy as a diagnostic tool for nail psoriasis has also been studied. [12][13][14][15] Although there are many studies delineating the clinical features of nail psoriasis, very few have described the histopathological features, or tried to correlate the two. In an attempt to bridge this gap, this descriptive cross-sectional study was undertaken to study the histopathological features of nail psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of nail clipping microscopy as a diagnostic tool for nail psoriasis has also been studied . Although there are many studies delineating the clinical features of nail psoriasis, very few have described the histopathological features, or tried to correlate the two.…”
Section: Introductionmentioning
confidence: 99%